A Study of Mortality in Burns (A review of 1513 cases) - Prof. R. C. Sinka; Dr. S. K. Verma (Indian Journal of Plastic Surgery)
1. Mortality among 1513 cases of burns admitted in Patna Medical college Hospital, TUnder Plastic Surgery Department from Jan., 1970 to Dec., 1979 were reviewed.